"И доконцавъ с нимъ миръ до своего живота": on the Question of the Context of the Opava Meeting in 1289, its Participants and the Eternal Czech-Galician Union - Kozak, S. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2021)
The article covers the circumstances of the meeting that took place in Opava in 1289 with the participation of the Czech king Wenceslaus II Přemyslid, Galician- Volynian suzerain Lev Danylovych and some Polish princes. As the Polish participants in the meeting are not named in the sources, there are still doubts in historiography as to who they were. An attempt was made to substantiate the version that one of the unnamed Polish participants in the meeting was Prince Władysław I Łokietek of Piast dynasty. This assumption is based on an analysis of the eventful context of the Opava meeting, which was part of the struggle for the Cracow heritage, as well as the matrimonial and dynastic ties that played a very important role in medieval international communication. It is noted that the union of Wenceslaus II, Lev Danylovych and Władysław I Łokietek repeatedly manifested itself shortly after the meeting in Opava and was based on existing dynastic ties and the conclusion of new marriage agreements. At the same time, the assumption that Prince Henryk IV Probus of Silesia may also have been present at the talks cannot be completely ruled out, although this hypothesis is currently less plausible. Lack of sources does not allow to definitively refute any of the versions. It is concluded that the Opava meeting was one of the key episodes of the Galician-Czech political union of the late XIIIth century and clearly demonstrated how relevant international communication was in the struggle for the Kraków throne. Lev Danilovych’s participation in the vicissitudes of the struggle for the Kraków throne is considered to be inextricably linked with the orientation towards an alliance with the Czech king and is connected with the importance of an ally of the Galician-Volynian ruler ruling in Kraków.